2020
DOI: 10.3390/nu13010001
|View full text |Cite
|
Sign up to set email alerts
|

Sweet but Bitter: Focus on Fructose Impact on Brain Function in Rodent Models

Abstract: Fructose consumption has drastically increased during the last decades due to the extensive commercial use of high-fructose corn syrup as a sweetener for beverages, snacks and baked goods. Fructose overconsumption is known to induce obesity, dyslipidemia, insulin resistance and inflammation, and its metabolism is considered partially responsible for its role in several metabolic diseases. Indeed, the primary metabolites and by-products of gut and hepatic fructolysis may impair the functions of extrahepatic tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 130 publications
(175 reference statements)
2
37
0
Order By: Relevance
“…Because SSBs were the principal source of added sugar in diets ( 43 ), it was reasonable to propose that the mechanism for explaining the association between SSBs intake and the emotional symptom was relevant to sugar content. First, several studies indicated that sugar intake resulted in a high risk of inflammation ( 44 , 45 ). A cohort study indicated that long-term inflammation increased the risk of common mental disorders ( 46 ), such as depression.…”
Section: Discussionmentioning
confidence: 99%
“…Because SSBs were the principal source of added sugar in diets ( 43 ), it was reasonable to propose that the mechanism for explaining the association between SSBs intake and the emotional symptom was relevant to sugar content. First, several studies indicated that sugar intake resulted in a high risk of inflammation ( 44 , 45 ). A cohort study indicated that long-term inflammation increased the risk of common mental disorders ( 46 ), such as depression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported relationships between the consumption of certain flavored beverages and brain activity [ 6 , 7 , 8 , 9 , 39 , 40 ]. However, most studies focus on links between beverage ingredients and brain regions or neural pathways, while less explore the relationship between taste and genes.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive consumption of fructose can lead to inflammation in the nervous system, microglial overactivation, and oxidative stress. Preclinical research has also suggested cognitive and memory impairment in rodents fed high concentrations of fructose [ 47 ] or sugar [ 48 , 49 ]. Sugar consumption impacts brain diseases or disorders, such as anxiety, depression, neurogenesis, fear, and changes in molecular and neurochemical expression [ 50 ].…”
Section: Introductionmentioning
confidence: 99%